THE DISCOURSE OF MATCHMAKING: GUILLEN’S THEMATOLOGY STUDY OF COMPARATIVE LITERATURE BETWEEN JANE AUSTEN'S PRIDE AND PREJUDICE AND HAMKA'S TENGGELAMNYA KAPAL VAN DER WIJCK - Hanifa Humaira; Aris Wuryantoro; Lusia Kristiasih Dwi Purnomosasi; Sigit Ricahyono (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
Comparative literature is made up of transnational assemblages. The literary works employed here include Jane Austen's Pride and Prejudice and HAMKA's Tenggelamnya Kapal Van Der Wijck. The purpose of this research is to identify a theme in order to determine the explanation for the theme in these two novels. The focus of this study is on the matching that takes place between England and Minangkabau, Indonesia. This study employed Guillen's (1993) Thematology to expose the theme's concept and a comparative literature method with documentation technique to collect data. The data categories are qualitative data gathered from original sources i.e.  Pride and Prejudice and Tenggelamnya Kapal Van Der Wijck. Thematic approach is be utilized to find patterns of the topics that are employed in the novels under investigation. This study concludes, not only women, but also men, are victims of matchmaking, which causes both parties to have a disadvantageous experience. Matching also causes men to suffer and women to rebel as a result of matchmaking that is impacted by economic factors, social status, and the meeting of old and new traditions.